1996
DOI: 10.1111/j.1476-5381.1996.tb16041.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective recognition of the enantiomers of phenglutarimide and of six related compounds by four muscarinic receptor subtypes

Abstract: 1 We have compared the binding properties of the enantiomers of phenglutarimide (1) and of six related compounds to M, receptors in NB-OK-1 cells, M2 receptors in rat heart, M3 receptors in rat pancreas and the M4 receptors of rat striatum, with their functional (antimuscarinic) properties in rabbit vas deferens (MI/M4-like), guinea-pig atria (M2) and guinea-pig ileum (M3) receptors. The binding properties of the enantiomers of three of the compounds were also measured on cloned human ml-m4 receptors expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Recently it was postulated that FPRs expressed in the vomeronasal organs of mammals have an olfactory function associated with the identification of pathogenic states [35], and Bufe et al [36] found that these receptors exhibited stereo-selective preference for peptides containing D-amino acids. Although numerous GPCR have been characterized as enantioselective receptors [18;19;37], including odorant receptors [38], only one example of enantioselective recognition of non-peptide ligands by FPRs has been observed previously [9]. The growing evidence implicating anti-inflammatory and tissue-protective effects of FPR agonists [16;17] and the recent development of novel chiral ligands as potential therapeutics and agonists of various GPCR [18;19;39] prompted us to search for novel non-peptide small-molecule enantiomeric FPR agonists [12;15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was postulated that FPRs expressed in the vomeronasal organs of mammals have an olfactory function associated with the identification of pathogenic states [35], and Bufe et al [36] found that these receptors exhibited stereo-selective preference for peptides containing D-amino acids. Although numerous GPCR have been characterized as enantioselective receptors [18;19;37], including odorant receptors [38], only one example of enantioselective recognition of non-peptide ligands by FPRs has been observed previously [9]. The growing evidence implicating anti-inflammatory and tissue-protective effects of FPR agonists [16;17] and the recent development of novel chiral ligands as potential therapeutics and agonists of various GPCR [18;19;39] prompted us to search for novel non-peptide small-molecule enantiomeric FPR agonists [12;15].…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit vas deferens has been one of the most used preparation for the putative muscarinic M 1 receptor ( Eltze, 1988 ; Eltze & Figala, 1988 ). However, emerging evidence indicates that the prejunctional rabbit vas deferens muscarinic receptors mediating inhibition of the neurogenic contractions may not belong to the M 1 subtype ( Caulfield & Brown, 1991 ; Caulfield, 1993 ; Sagrada et al ., 1994 ; Waelbroeck et al ., 1996 ). A possible explanation for the confusion arising in receptor classification may be that putative muscarinic M 1 receptors have long been identified as the sites which bind pirenzepine with high affinity ( Hammer et al ., 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cloned receptors have been used to determine the potency of novel compounds and to determine the subtype selectivity of antimuscarinic agents (30)(31)(32). Currently, several muscarinic receptor subtype-selective agents are in advanced clinical trials (33,34).…”
Section: Introductionmentioning
confidence: 99%